Proceedings of the 3rd Italian-Polish conference on applications of systems theory to economy, management and technology: Białowieża, Poland, May 26-31, 1976 * Systems theory of economic * On optimum allocation of resources - Cichocki, Krzysztof (Instytut Badań Systemowych. Polska Akademia Nauk, 1977)
This paper develops a model of economic growth designed to provide framework for optimal allocation of resources such as labour, capital and public consumption services. The resorces are assumed to be the result of savings over a time interval (O, T). The savings come from two sources : depreciation allowances and household savings. Mathematically the problem is characterized by a nonlinear dynamie system. The objective of the system is to maxirnize the net national product over (O, T). The problem possesses a unique global optimal solution expressible in exogenous variables. An extension of the model is possible which provides a framework for dealing with optimal selection of prices and deterrnining the optima! level of savings, satisfying dernands of production for resources.
[4], 175-191 stron ; 21 cm
Bibliografia s. 190